Orthotopic Human Metastatic Uveal Melanoma Xenograft Mouse Models: Applications for Understanding the Pathophysiology and Therapeutic Management of Metastatic Uveal Melanoma. Issue 4 (21st April 2021) - Terai, Mizue; Kageyama, Ken; Sugase, Takahito; Lam, Bao Quoc; Alexeev, Vitali; Sato, Takami
Abstract: The propensity of uveal melanoma to metastasize to the liver hinders the accrual of micro‐metastatic and end‐stage disease tissue samples and restricts the investigation of metastatic uveal melanoma (MUM). Pre‐clinical experimental animal models of MUM can help elucidate the pathophysiology of metastatic lesions and provide a tool for designing new therapeutic approaches for MUM. Here, we present an advanced model of hepatic metastases that enables quantitatively visualizing the development of individual hepatic tumor clones and estimating their growth kinetics and colonization efficiency. Similar to clinically observed liver metastases, these models enable the assessment of growth kinetics of the liver micro‐metastases and the testing of therapeutic approaches for the treatment of MUM. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Experimental patient‐derived xenograft mouse model of metastatic uveal melanoma Basic Protocol 2 : Experimental liver micro‐metastatic mouse model using splenic injection of metastatic uveal melanoma cells